(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discusses the methodology of reflection of the creative technologies of the years of Uzbekistan’s visual arts, pen drawing, painting, composition, new ideas, and the historical significance of the theoretical foundations of the creative works of famous artists.